(untitled) (Foro de Educacion, 2023)
This article discusses the approach of educational policies in Chile, which promote a curricular approach towards the nature of exploiting resources, functional in a country that bases its economy on the export of raw materials. Through a review of different bibliographic sources, the installation of this functionalist approach, which we call pedagogy of extractivism, is analyzed as part of a globalized economic system of neoliberal market that originated from the expansion of industrialism, installed as the only way of development for countries, which has generated social conflicts and pollution levels that have precipitated climate change. Education is a tributary of these hegemonies because the school has historically been linked to the productive apparatus of modernity after the Industrial Revolution, first with the factory and then with the company, laying the foundations for an «industrial society». After exploring the relationship between school knowledge and indigenous knowledge, it concludes by proposing the articulation between the knowledge of the mapuche people and schoolchildren, as a way for a pluralistic education that generates social change, towards another relationship with nature and other forms of development, aimed at environmental conservation.